Use of O-arm to place an intrathecal catheter through a bony fusion mass: case report - Sammartino, Francesco; Bavishi, Sheital; Dalm, Brian (Frontiers in Rehabilitation Sciences, 2025)
BackgroundIntrathecal baclofen (ITB) delivery is an FDA-approved indication for patients with intractable spasticity. Often, implantation in these patients can be considerably challenging, especially if previous surgical fusion involves the procedure access location.Case report We present the case of a 27-year-old female with T2 American Spinal Injury Association (ASIA) A spinal cord injury (SCI) and chronic spastic dystonia. She was maximized on oral medications without satisfactory control of her painful muscle spasms and was a candidate for ITB trial, which ultimately failed due to the difficulty of accessing the spinal canal due to extensive pseudoarthrosis secondary to thoracic to lumbar fusion. A decision was made to directly implant the pump in the operative room using O-arm–aided neuronavigation to guide catheter access at L5–S1. Currently, at 22 months of follow-up post-pump implant, ITB delivery has led to persistent improvements in her spastic dystonia and many aspects of quality of life.Discussion The current case indicates that a multidisciplinary approach when considering surgical treatments for medication-refractory spasticity may help expand the indications to large numbers of patients with postsurgical spine abnormalities.